The Typology of The Kost-Shop Friendly Facades in The Reproduction of Social Interaction Space based on The Needs and Opportunities between Kampung and Campus - Pasaribu, Ramos Panondang; Tobing, Rumiati R; Siahaan, Uras (Jurnal Teknik Sipil dan Perencanaan, 2020)
One interesting phenomenonÃ‚Â  found in Indonesia to date is Ã¢â‚¬Å“living and growing in a city with the characteristic features of a Kampung (urban village) with all of its distinctive facesÃ¢â‚¬Â, like the interdependent relations between the Kampung Kemanggisan around the Syahdan Campus of Bina Nusantara Jakarta. The students find their daily needs in the Kampung and the villagers find business opportunities and reproduce the Ã¢â‚¬Å“Social Interaction SpaceÃ¢â‚¬Â along the Haji Senin street (study location) which is dominated by buildings with the ground floor as a place of business and the upper floor as a Kost or the private housings with rented rooms which in this study was called the Ã¢â‚¬Å“Kost-ShopÃ¢â‚¬Â building. Variations of the Ã¢â‚¬Å“Pedestrian-Friendly Kost-ShopÃ¢â‚¬Â building grew and had an impact on the appearance of the facade. This study to reveal and provides an understanding of typology of Ã¢â‚¬Å“Kost-Shop Friendly FacadesÃ¢â‚¬Â that exists based on student Ã¢â‚¬Å“Needs and the OpportunitiesÃ¢â‚¬Â, therefore, this study was written with the title of Ã¢â‚¬Å“Kost-Shop FacadesÃ¢â‚¬Â in Ã¢â‚¬Å“the Reproduction of Social Interaction SpaceÃ¢â‚¬Â based on the Ã¢â‚¬Å“Needs and OpportunitiesÃ¢â‚¬Â between Kampung and Campus. By using qualitative research methods; case study with indications of Ã¢â‚¬Å“social, permeable, activeÃ¢â‚¬Â obtained 12 types of Ã¢â‚¬Å“Kost-Shop Friendly FacadesÃ¢â‚¬Â.